Increasing precipitation during first half of growing season enhances ecosystem water use efficiency in a semiarid grassland - Zhang, Jiayang; Yang, Zhongling; Qiao, Daiyu; Su, Lei (Frontiers in Plant Science, 2023)
Precipitation amount and seasonality can profoundly impact ecosystem carbon (C) and water fluxes. Water use efficiency (WUE), which measures the amount of C assimilation relative to the amount of water loss, is an important metric linking ecosystem C and water cycles. However, how increasing precipitation at different points in the growing season affects ecosystem WUE remains unclear. A manipulative experiment simulating increasing first half (FP+) and/or second half (SP+) of growing-season precipitation was conducted for 4 years (2015-2018) in a temperate steppe in the Mongolian Plateau. Gross ecosystem productivity (GEP) and evapotranspiration (ET) were measured to figure out ecosystem WUE (WUE = GEP/ET). Across the four years, FP+ showed no considerable impact on ecosystem WUE or its two components, GEP and ET, whereas SP+ stimulated GEP but showed little impact on ET, causing a positive response of WUE to FP+. The increased WUE was mainly due to higher soil water content that maintained high aboveground plant growth and community cover while ET was stable during the second half of growing season. These results illustrate that second half of growing-season precipitation is more important in regulating ecosystem productivity in semiarid grasslands and highlight how precipitation seasonality affects ecosystem productivity in the temperate steppe ecosystem.